HUBUNGAN KEAKTIFAN BELAJAR DENGAN CAPAIAN EVALUASI KOGNITIF PESERTA DIDIK PADA MATERI AKUNTASI PERUSAHAAN JASA - Habibullah, Habibullah; Genjik S, Bambang; Okianna, Okianna (Universitas Tanjungpura, 2023)
Student Learning Activeness with the Achievement of Cognitive Assessment of Class XII Students Accounting for Services Company MA Darul Hidayah. The method used in this study uses quantitative methods in the form of correlation or correlation research. Data collection techniques using questionnaires, unstructured interviews and documentaries. The tools used in data collection are distributing questionnaires and documentation. The sample used is saturated sampling technique involving all correspondents. In this study, it was seen that there was a significant relationship between learning activeness and the results of students' cognitive evaluations which showed a correlation coefficient of 0.800. while the coefficient of determination in this study shows a very significant relationship between learning activeness as variable X and cognitive learning achievement as variable Y which is equal to 0.722. When calculating the linear correlation, the equation Y = 16.668 + 0.149 is obtained, which means that the constant value is 16.668. If student learning activeness is worth 0, then learning activeness is 0.149 which means an increase in learning activeness by 1 will increase cognitive evaluation achievement by 14.9%.